Bacillus Calmette-Guérin may have clinical benefit for glandular or squamous differentiation in non-muscle invasive bladder cancer patients: retrospective multicenter study. (4th May 2018) - Yorozuya, Wakako; Nishiyama, Naotaka; Shindo, Tetsuya; Kyoda, Yuki; Itoh, Naoki; Sugita, Shintaro; Hasegawa, Tadashi; Masumori, Naoya
Abstract : The aim of this study was to clarify the clinical efficacy of BCG treatment for NMIBC patients with variant histology. BCG treatment may also have a clinical benefit for variant histology. Abstract: Objectives: To clarify the efficacy of intravesical Bacillus Calmette-Guérin (BCG) instillation for non-muscle invasive bladder (NMIBC) cancer with variant histology, especially glandular differentiation or squamous differentiation. Materials and methods: From May 1991 through June 2016, 53 patients were diagnosed retrospectively as having NMIBC with variant histology. Among these patients, 47 NMIBC patients with squamous differentiation or glandular differentiation were analyzed for this study. The median follow-up interval from diagnosis of NMIBC with variant histology was 28.9 months (1.5–168.8). Results: Of these patients, 38 (80.9%) and 9 (19.1%) were diagnosed as having glandular differentiation and squamous differentiation, respectively. Radical cystectomy was conducted for six (12.8%) immediately after the diagnosis of NMIBC with variant histology. Of the 41 patients with bladder preservation, 20 (48.8%), 3 (7.3%), 3 (7.3%) and 15 (36.6%) underwent BCG, THP, MMC and no additional treatment, respectively. There were significant differences between BCG and other treatments or no additional treatment for recurrence ( P = 0.034), progression ( P = 0.004) and cancer-specific survival ( P = 0.014). Conclusion: Overall, our results show that intravesical BCG instillation for variant histology in NMIBC leads to a better prognosis with regard to progression and cause-specific survival than other intravesical treatments or no additional treatment. BCG treatment may also have a clinical benefit for variant histology in non-muscle invasive bladder cancer patients.